Is trade liberalization, economic growth, energy consumption good for the environment? - Asma Jabeen (Romanian Journal of Fiscal Policy (RJFP), 2015)
The study attempts to identify the dynamic relationship between trade, income growth, energy consumption and CO2 emissions for Pakistan. Johansen's Cointegration procedure has been employed to estimate the coefficients of the Cointegrated Vector Autoregressive model. The results reveal that trade has a favorable effect on environmental quality for Pakistan economy, while income growth, energy consumption tends to worsen the environmental quality thus supporting the existence of Environmental Kuznet Curve for Pakistan.
Keywords: F1; N7; O4; 330; Trade; Energy consumption; Economic growth; Environment quality; Cointegrated VAR